[tex]( – 4) + ( + 9) = \\ ( – 7) – ( + 1) = \\ ( + 63) \div ( – 7) = \\ ( – 2) \times ( + 5) = \\ ( – 5) – ( + 3) = \\

Question

( - 4) + ( + 9) =  \\ ( - 7) - ( + 1) =  \\ ( + 63) \div ( - 7) =   \\ ( - 2) \times ( + 5) =  \\ ( - 5) - ( + 3) =  \\ ( + 8) - ( + 6) =

in progress 0
Katherine 2 months 2021-08-01T10:25:22+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-01T10:26:33+00:00

    Step-by-step explanation:

    1)5 \\ 2) - 8 \\ 3)9 \\ 4) - 10 \\ 5) - 8 \\ 6)2

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )